Evaluation of the Relation Between Omentin-1 and Vitamin D in Postmenopausal Women With or Without Osteoporosis - Dikker, Okan; Bekpinar, Seldag; Ozdemirler, Gul; Uysal, Mujdat; Vardar, Muberra; Atar, Sevgi; Usta, Murat; Huner, Berrin (Experimental and Clinical Endocrinology & Diabetes, 2018)
Introduction Crosstalk between bone and adipose tissues is implicated in several pathologic conditions related to bone metabolism. Omentin-1, a 34-kD protein, is released from omental adipose tissue. A few studies indicated the effect of omentin-1 on bone health and bone mineral density (BMD) and the interaction of omentin-1 with vitamin D. Therefore, this study aimed to investigate the relationship between omentin-1, vitamin D, and BMD in postmenopausal women with osteoporosis compared with non-osteoporotic counterparts.Materials and methods Forty postmenopausal women with osteoporosis (OP), 40 counterparts without OP, and 30 premenopausal women were enrolled. Dual-energy X-ray Absorptiometry results, body mass index, and some demographic and biochemical data were recorded. Vitamin D (25-hydroxyvitamin D3) levels were measured using liquid chromatography-tandem mass spectrometry. Serum omentin-1 was determined using an enzyme-linked immunosorbent assay.Results Omentin-1 levels tended to increase in both postmenopausal women groups compared with the control group, but this increase was significant only in women with osteoporosis. Vitamin D levels were not different between the groups. When women were categorized according to vitamin D levels, women with normal vitamin D levels had significantly higher omentin-1 levels. A positive correlation was found between omentin-1 and vitamin D levels in all groups (r=0.197, p=0.041, n=110).Conclusion The tendency to an increase in omentin-1 levels in postmenopausal women with osteoporosis may be due to a physiologic compensation against bone loss after menopause. The linear relationship between omentin-1 and vitamin D suggests that adipose tissue is one of the target tissues for the vitamin D effect.
Keywords: omentin-1; vitamin D; osteoporosis; bone mineral density